Abundance, prey, and activity period of dholes (Cuon alpinus) in Khao Yai National Park, Thailand - NORASET KHOEWSREE; KHWANRUTAI CHARASPET; ronglarp - sukmasuang; NUCHARIN SONGSASEN; MANANYA PLA-ARD; JIDAPA THONGBANTUM; WARAPORN KONGCHALOEM; KHANCHIT SRINOPAWAN (Society for Indonesian Biodiversity, 2020)
Abstract. Khoewsree N, Charaspet K, Sukmasuang R, Songsasen N, Pla-ard M, Thongbantum J, Kongchaloem W, Srinopawan K. 2020. Abundance, prey, and activity period of dholes (Cuon alpinus) in Khao Yai National Park, Thailand. Biodiversitas 21: 345-354. The abundance and occupancy of dholes in Khao Yai National Park are the highest among found carnivorous mammals. This demonstrates the importance of the home range of dholes. From the scat analysis, eight species of mammals that are prey can be identified. The dholes mainly consume ungulates when considering the most percentage of relative biomass consumed were ungulate species. For the number of prey animals consumed by dholes per year, a dhole consumes 25.94 prey animals per year which consist of 6.51 masked palm civets, 6.44 Asian palm civets, 4.55 muntjac, 3.97 lesser mouse-deer, 2.22 large Indian civets, 1.03 wild boars, 0.66 sambar, and 0.56 porcupines. From the daily activity pattern captured by the camera trap, dholes have an average activity period of 14:49 hours. Therefore, they are mostly diurnal. The results of the study confirm that Khao Yai National Park is an important habitat of dholes. To maintain the population of dholes in the area, the most important factor is maintaining the ungulate population in the area, especially muntjac, sambar, lesser mouse-deer, and wild boar by increasing and improving the quality of grassland, austerity of maintenance, garbage and dirt disposal from tourism activities in the area for ecological health, and public relations for dholes’ conservation in the long-term.